Al-‘Aruḍ fī al-Syi‘ri “Min Tajārubi al-Imām ma‘a al-Ayyām ma‘a al-Nafsi ma‘a al-Qaḍāi” Li al-Imām al-Syaf‘ī” - Nurcholis, Agung; Khoiry, Ulfi Usykuriyah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This study examines the poem min tajārubi al-imām ma‘a al-ayyām ma‘a al-annafsi ma‘a al-qaḍāi by Imām Asy-Syaf‘ī in terms of ‘aruḍ. And this study is within the desk study, and the methods of data collection in this way are the methods of data collection by the documentary method and as for data analysis by descriptive analysis and content analysis and the main data of this research is the poem min tajārubi al-imām ma‘a al-ayyām ma‘a al-annafsi ma‘a al-qaḍāi by Imām Asy-Syaf‘ī in terms of ‘aruḍ. The result of the study the poem min tajārubi al-imām ma‘a al-ayyām ma‘a al-annafsi ma‘a al-qaḍāi by Imām Asy-Syaf‘ī in terms of ‘aruḍ found rythms of musicality that exist in this poem namely using the types of bahr wafir, in this sudy found zihaf the name is ‘asb in this poem form rythms “mufā’alatun” to “mufā’altun” which in the stanzas: 1,2,3,5,6,7,8,9,10,11,12,13. In this study not found ‘illah because bahr wafir does not find ‘illah.